Effectiveness Utilization of Village Funds in Development of MSMEs (Case Study: Tambang Sub-District, Kampar) - Pendri, Agus; Zulher, Zulher; Kasmawati, Kasmawati (Dinasti Publisher, 2026)
The purpose of this study is to analyze the effectiveness of Village Fund utilization in the development of Micro, Small, and Medium Enterprises (MSMEs) in Tambang District, Kampar Regency. Village Funds are an important instrument in village development that is directed not only at infrastructure development, but also at empowering the community economy, especially MSMEs. the research method uses a descriptive approach with SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis techniques. Data were collected through in-depth interviews, field observations, and review of official village documents. the research results show that the utilization of Village Funds has significantly contributed to the development of MSMEs, particularly in terms of business group capital, skills training, and the provision of production facilities. However, its effectiveness has not been maximized due to weaknesses in business management, product innovation, and limited market access. A SWOT analysis yielded several development strategies, including optimizing local potential (traditional culinary, plantation products, and crafts), strengthening the capacity of MSMEs through management training and digitalization, product diversification, and strengthening village business institutions.